Flow experience and city identity in the restorative environment: A conceptual model and nature-based intervention - Xie, Mei; Mao, Yanhui; Yang, Rui (Frontiers in Public Health, 2022)
Within environmental psychology, the restorative environment is receiving increasing attention due to its favorable impact on people's mental recovery, stress reduction, and psychophysiological well-being. Flow theory, as one of the foundations of positive psychology, is a popular theoretical framework for understanding human flourishing and well-being. The restorative environment is suggested to facilitate flow experience and city identity from the perspective of positive environmental psychology. Nonetheless, systematic research investigating them all together can hardly be traced. Thus, through a preliminary review of 169 relevant studies retrieved from the data source, this work proposes a novel theoretical model in which people's interactions within the restorative environment facilitate their experience of flow and perceived city identity. Additionally, this research provides conceptual guidance for city workers to engage in nature-based intervention and leisure therapy for improved well-being. Overall, this review endeavors to contribute to developing urban workers' restoration, happiness, and well-being from both practical and theoretical perspectives.